Co-enrichment of CD8-positive T cells and macrophages is associated with clinical benefit of tislelizumab in solid tumors - Dingwei Ye; Jayesh Desai; Jingwen Shi; Si-Yang Maggie Liu; Wei Shen; Tengfei Liu; Yang Shi; Dan Wang; Liang Liang; Silu Yang; Xiaopeng Ma; Wei Jin; et al. (BMC, 2023)
Abstract Background Activated immune cells (IC) in the tumor microenvironment (TME) are critical for anti-tumor efficacy. Greater understanding of the dynamic diversity and crosstalk between IC is needed to clarify their association with immune checkpoint inhibitor efficacy. Methods Patients from three tislelizumab monotherapy trials in solid tumors (NCT02407990, NCT04068519, NCT04004221) were retrospectively divided into subgroups by CD8+ T-cell and macrophage (Mφ) levels, assessed via multiplex immunohistochemistry (mIHC; n = 67) or gene expression profiling (GEP; n = 629). Results A trend of longer survival was observed in patients with both high CD8+ T-cell and Mφ levels versus other subgroups in the mIHC analysis (P = 0.11), which was confirmed with greater statistical significance in the GEP analysis (P = 0.0001). Co-existence of CD8+ T cells and Mφ was coupled with elevated CD8+ T-cell cytotoxicity, T-cell trafficking, MHC class I antigen presentation signatures/genes, and enrichment of the pro-inflammatory Mφ polarization pathway. Additionally, a high level of pro-inflammatory CD64+ Mφ density was associated with an immune-activated TME and survival benefit with tislelizumab (15.2 vs. 5.9 months for low density; P = 0.042). Spatial proximity analysis revealed that closer proximity between CD8+ T cells and CD64+ Mφ was associated with a survival benefit with tislelizumab (15.2 vs. 5.3 months for low proximity; P = 0.024). Conclusions These findings support the potential role of crosstalk between pro-inflammatory Mφ and cytotoxic T cells in the clinical benefit of tislelizumab. Trial registration NCT02407990, NCT04068519, NCT04004221.